ANALYSIS OF TRACING ABILITY OF DIFFERENT SIZED PARTICLES IN DRIP IRRIGATION EMITTERS WITH COMPUTATIONAL FLUID DYNAMICS1. (10th June 2013) - Li, Yunkai; Liu, Haisheng; Yang, Peiling; Wu, Dan; Schultz, Bart
ABSTRACT The tracing ability of particles in the flow path is the key to digital particle image velocimetry (DPIV) testing and clogging control in drip irrigation emitters. Six different kinds of particles with respective diameters of 0.01, 0.02, 0.04, 0.05, 0.06 and 0.08 mm were considered, and the tracing ability was carried out by using the computational fluid dynamics (CFD) turbulence simulation method. Results showed that standard k‐ε model could well describe the transportation process of particles in drip irrigation emitters in terms of precision, applicable extensibility and computational expense. Clogging most likely occurred in the corner of the whole flow path of the drip irrigation emitter region, sections 1 and 8 plus sections 4 and 5. The tracing ability of the particles of 0.01 mm diameter was good enough to be used for a single‐phase test. And for a two‐phase test, diameters of the particles should be more than 0.04 mm. Copyright © 2013 John Wiley & Sons, Ltd.